Petunjuk Pelaksanaan Validasi Metode Dan Cara Perhitungannya - Harmita, Harmita (UI Scholars Hub, 2004)
Each analysis method by some reason, must be validated. The parameters are selectivity, accuracy, precision, linearity, LOD, LOQ, ruggedness, and robustness. The parameters need to be calculated by assay methods. This paper try to give some information above these methods base on some literatures (USP 23rd, WHO, journal, etc).